Bichromatic visual stimulus with subharmonic response to achieve a high-accuracy SSVEP BCI system with low eye irritation. (May 2023) - Vahid, Farnoosh; Behboodi, Mohammadreza; Mahnam, Amin
Highlights: The proposed bichromatic visual stimulus has a color-based subharmonic response in the low-frequency range besides the primary high-frequency response. The average accuracy over 16 subjects for this stimulus is significantly higher than conventional high-frequency stimulus. The average score provided by the subjects for eye irritation is significantly lower for this stimulus compared to the reference stimulus. Significant improvement in both performance and irritation score of the proposed visual stimulus is a substantial achievement for the practical use of SSVEP BCI systems. The function of chromatic and luminescence-sensitive pathways in the visual system can provide a rationale for the higher performance of the proposed visual stimulus. Abstract: Objective: While various Steady State Visual Evoked Potential Brain-Computer Interfaces (SSVEP BCI) with very high performance have already been developed, eye irritation is a significant burden in their practical use. Generally, there is a tradeoff between eye irritation and BCI accuracy. However, this study proposes a bichromatic visual stimulus with low eye irritation while providing accurately detectable electroencephalogram responses. Methods: The proposed visual stimulus, which is high-frequency in terms of luminance but with a subharmonic color component, was compared to the conventional high-frequency SSVEP on 16 subjects. Canonical Correlation Analysis, Least Absolute Shrinkage and Selection Operator, Multivariate Synchronization Index (MSI), and Extended MSI were used separately to recognize aimed visual stimuli in a 4-target BCI system. Results: The proposed stimulus resulted in significantly (p-value = 0.024) higher accuracy (96 ± 4.1%) compared to the reference (87.1 ± 14.6%) for a processing window of 4.5 s using the Extended MSI algorithm. Eye irritation scores (3.8 ± 1.0 on a 1–9 scale) were also significantly lower (p-value = 0.035) than that of the reference stimulus (4.3 ± 1.1). No cases of illiteracy were observed with the proposed waveform, whereas there were 2 with the reference stimulus. Conclusion: The proposed bichromatic waveform provided significantly higher accuracy, especially for users who do not have strong high-frequency SSVEP responses. Eye irritation was also significantly lower than with conventional reference visual stimulus. The proposed visual stimulus can generate electroencephalogram responses, not only in the high-frequency range but also at half the main frequency. Significance: The results are significant for realizing practical, accurate SSVEP BCI systems.